Moderate PM10 exposure increases prostate cancer: a longitudinal nationwide cohort study (2010–2020) - Rho, Mi Jung; Park, Yong Hyun; Park, Jihwan (Frontiers in Public Health, 2025)
IntroductionFine dust exposure has been reported to affect patients with prostate cancer, making it crucial to understand how environmental pollutants impact health. This study aimed to determine the risk of prostate cancer in South Korea associated with moderate levels of fine dust (PM10) exposure.MethodsWe analyzed data from 20,430 individuals in the National Health Insurance Sharing Service database from 2010 to 2020, comparing a new prostate cancer group (n = 4,071, 19.9%) with a non-prostate cancer group (n = 16,359, 80.1%). Using PM10 data from Air Korea's annual average air quality database, we conducted logistic regression analysis to assess the risk of prostate cancer.ResultsOur findings indicate that even moderate PM10 exposure is a risk factor for developing prostate cancer. Additionally, even at low levels of PM2.5, moderate PM10 exposure significantly impacts prostate cancer development, with lifestyle ha bits potentially lowering this risk.DiscussionThese results underscore the need for stricter environmental standards for PM10 and proactive policies to reduce public health and long-term social costs. Public awareness, including mask use and air quality management, is essential.